Design of Library Collection Procurement System in Bali - Suhartika, I Putu; Punia, I Nengah; Haryanti, Ni Putu Premierita; Sujana, A. A. Putu Oka (Program Studi Ilmu Perpustakaan UIN Alauddin, 2024)
The process of library collection development encompasses several crucial tasks, including identification, selection, acquisition, processing, and distribution of collections to the public. This study endeavors to develop a library collection procurement application focusing on two primary functionalities: selection and procurement. The system accommodates stakeholders, including publishers, librarian profiles, system masters, and other users, while adhering to specific user and system requirements. The design methodology employed in this study leverages the Unified Modeling Language (UML). The development process follows the waterfall method, encompassing stages such as requirements analysis, design, implementation, verification, and maintenance. The resulting application features an intuitive interface for collection procurement, incorporating essential components such as login mechanisms, a comprehensive book collection database, catalog data management, procurement selection tools, recommendation algorithms, catalog selection options, and access to selected catalog data. Employing the CodeIgniter (CI) framework, the system facilitates data filtration and selection processes based on publication year, price, and language criteria. Rigorous system testing, conducted through black box testing methods, confirms the functionality and reliability of the application. This research contributes to addressing the needs of libraries lacking robust collection procurement systems, offering a sophisticated solution to streamline and automate traditionally manual processes.